2013
DOI: 10.1371/journal.pone.0076058
|View full text |Cite
|
Sign up to set email alerts
|

S100A14 Interacts with S100A16 and Regulates Its Expression in Human Cancer Cells

Abstract: Both S100A14 and S100A16 are members of the multifunctional S100 protein family. Formation of homo/heterodimers is considered to be one of the major mechanisms for S100 proteins to execute their diverse cellular functions. By employing a classical Yeast two hybrid (Y-2 H) screen, we identified S100A16 as the single interaction partner of S100A14. This interaction was verified by co-immunoprecipitation, double indirect immunofluorescence and double immunostaining in specimens of oral squamous cell carcinoma and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
25
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 31 publications
2
25
0
Order By: Relevance
“…The elevation of S100A16 induced by HBMEC exosomes facilitated the survival of SCLC cells It has been reported that S100A16 is up-regulated in several cancer tissues, suggesting a function related to malignant transformation or tumor development (14)(15)(16). Our results from the above clinical data indicate that the elevation of S100A16 was associated with SCLC metastasis to the brain.…”
Section: Resultssupporting
confidence: 62%
See 1 more Smart Citation
“…The elevation of S100A16 induced by HBMEC exosomes facilitated the survival of SCLC cells It has been reported that S100A16 is up-regulated in several cancer tissues, suggesting a function related to malignant transformation or tumor development (14)(15)(16). Our results from the above clinical data indicate that the elevation of S100A16 was associated with SCLC metastasis to the brain.…”
Section: Resultssupporting
confidence: 62%
“…The coexpression of S100A16 and S100A14 has been associated with a poor prognosis in patients with breast cancer. These protein interactions could promote the invasive activity of breast cancer cells via an interaction with cytoskeleton dynamics (15). In addition, the up-regulation of S100A16 promoted epithelial-mesenchymal transition via the Notch1 pathway in the breast cancer cell line MCF-7 (16).…”
mentioning
confidence: 99%
“…Compared to S100A16, S100A14, another member of the S100 family, has been studied in more depth. S100A14 was shown to be the sole interaction partner of S100A16 in OSCC . In addition, genome‐wide functional coupling networks database also showed that S100A16 was the main partner of the S100A14 protein .…”
Section: Discussionmentioning
confidence: 92%
“…Abnormal expression of S100A16 was found in many tumours, such as cancer of the breast cancer, prostate and lung, suggesting a function related to malignant transformation or tumour development (Marenholz & Heizmann, ). For example, the co‐expression of S100A14 and S100A16 correlated with a poor prognosis in human breast cancer and promoted the invasive activity of breast cancer cells via an interaction with cytoskeletal dynamics (Sapkota et al , ). High S100A16 expression was found to be significantly associated with a poor prognosis in lung, prostate and breast cancers (Saito et al , ).…”
mentioning
confidence: 99%